Circulating Tumor Cells and Circulating Tumor DNA in Colorectal Cancer. Issue 2 (3rd March 2016) - Mohamed Suhaimi, Nur-Afidah; Tan, Min-Han
ABSTRACT: Genetic alterations in cancers serve as useful biomarkers in evaluating diagnosis, prognosis, and therapeutics. Genotyping tumour biopsies has become a routine practice in clinical oncology; however, it can only provide a spatially and temporally limited snapshot of the tumour achieved through an invasive procedure at a single time point. Circulating tumour cells (CTCs) or cell-free circulating DNA (cfDNA) could allow both qualitative and quantitative insights on disease activity in a non-invasive manner. Such genetic testing in blood is challenging owing to the rarity of the mutant alleles and cells, but advances in diagnostics have allowed strategies for longitudinal monitoring of the genetic landscape of cancer. We review here approaches to investigate these biomarkers in the blood and discuss the corresponding insights lent to diagnostic testing, tumour heterogeneity and therapeutic guidance, with a focus on colorectal cancer.